2015
DOI: 10.1016/j.medici.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-oxidative effects of herbal preparation EM 1201 in adjuvant arthritic rats

Abstract: The present study suggests that EM 1201 has protective activity against arthritis and demonstrated its potential beneficiary effect analogical to diclofenac. Anti-inflammatory and anti-oxidative effect of EM 1201 in rats with AA support the need of further investigations by using it as supplementary agent alone or together with other anti-arthritic drugs in the treatment of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…This effect of the herbal formulations was comparable to that obtained from the orthodox drug used for this study. This finding agrees with the work of Akramas et al [39] who reported similar findings using EM1201, a polyherbal formulation and diclofenac, an orthodox drug. Natural substances exert their medicinal effects in ways similar to allopathic medicines; they inhibit the pathways of inflammation [40].…”
Section: Discussionsupporting
confidence: 93%
“…This effect of the herbal formulations was comparable to that obtained from the orthodox drug used for this study. This finding agrees with the work of Akramas et al [39] who reported similar findings using EM1201, a polyherbal formulation and diclofenac, an orthodox drug. Natural substances exert their medicinal effects in ways similar to allopathic medicines; they inhibit the pathways of inflammation [40].…”
Section: Discussionsupporting
confidence: 93%
“…This was accompanied by an increase in the circulation of inflammatory cells, which was confirmed by an increase in spleen weight and erythrocyte sedimentation rate. It has also been shown that cytokines released by inflamed synovial tissue can reach systemic circulation and act on other organs as proven in this study and by others [7, 21, 39, 40]. The systemic manifestations of arthritis were confirmed by a dramatic drop in the rats’ body weight and by impairing the liver.…”
Section: Discussionsupporting
confidence: 82%
“…MDA was increased during RA, suggesting that MDA was deemed a critical injury mechanism. A decrease in GSH could impair the clearance of H2O2 and support OH formation, enhancing the free radical load that leads to homeostasis disturbance . In addition, many trials have shown that there is a lot of oxidative stress in RA patients and this oxidative stress can lead to overproduction of cytokines and harm to the joint tissue .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in GSH could impair the clearance of H2O2 and support OH formation, enhancing the free radical load that leads to homeostasis disturbance. [30][31][32] In addition, many trials have shown that there is a lot of oxidative stress in RA patients and this oxidative stress can lead to overproduction of cytokines and harm to the joint tissue. 33,34 CFA rats have been shown to have reduced antioxidant enzyme activity in the plasma, such as SOD, CAT, and GSH, and some trials have shown that these antioxidant enzymes have RA impacts.…”
Section: Discussionmentioning
confidence: 99%